2002
DOI: 10.1081/ddc-120003453
|View full text |Cite
|
Sign up to set email alerts
|

Stability-Indicating Spectrophotometric and Densitometric Methods for Determination of Aceclofenac

Abstract: Three methods were developed for the determination of aceclofenac in the presence of its degradation product, diclofenac. In the first method, third-derivative spectrophotometry (D3) is used. The D3 absorbance is measured at 283 nm where its hydrolytic degradation product diclofenac does not interfere. The suggested method shows a linear relationship in the range of 4-24 micrograms mL-1 with mean percentage accuracy of 100.05 +/- 0.88. This method determines the intact drug in the presence of up to 70% degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…1. Literature survey revealed various analytical methods, for example spectrophotometric, colorimetric, HPLC, and stability-indicating HPTLC methods for analysis of ACF alone and in combination with other drugs in pharmaceutical formulations [8][9][10][11][12][13][14][15][16]. A variety of methods have been used for analysis of PCM [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…1. Literature survey revealed various analytical methods, for example spectrophotometric, colorimetric, HPLC, and stability-indicating HPTLC methods for analysis of ACF alone and in combination with other drugs in pharmaceutical formulations [8][9][10][11][12][13][14][15][16]. A variety of methods have been used for analysis of PCM [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This approach depends on differentiation of the regular absorption spectrum using arithmetical transformation into a first-order derivative or a higher order derivative. Several advantages are achieved using DS including but not limited to an improvement in resolution, reduction of noise level, elimination of interferences, augmentation of sensitivity and selectivity, and accordingly an improvement in separation efficiency [51][52][53][54].…”
Section: Spectroscopic Analyses -Developments and Applicationsmentioning
confidence: 99%
“…For ACF methods reported are spectrophotometry [12,13], stability indicating HPLC [14], UPLC [15] and HPTLC [16,17] either alone or in combination with other drugs. It was further revealed that there are analytical methods reported for simultaneous estimation of PCT and ACF like Spectrophotometry [18], HPLC [19][20][21], HPTLC [22], stability indicating HPLC [23] while few reported methods like HPLC [24], HPTLC [25] and stability indicating HPTLC [26] involve simultaneous estimation of PCT and ACF combined with one more additional drug.…”
Section: Aceclofenac (Acf) Is Chemically 2-[2-[2-[(26-dichlorophenylmentioning
confidence: 99%